Coping with Environmental Standards in Trade: Indonesian Experience with Sustainable Palm Oil Debate - Maharani Hapsari (Journal of World Trade Studies, 2011)
Managing environmental standards as a form of environment-related trade barriers has become increasingly important for producing countries that are active participants in global commodity trading. Current international environmental standardization in trade, shows stronger tendency of convergence between sustainability criteria developed by the private sector and government regulations that apply in importing countries. Subsequently, such standards have overtime become guidelines for policy reforms in producing countries. To that end, the increasing role of private actors in pushing for higher environmental standards, has generated new dynamics in production-trade relations, which have overtime become increasingly complex. As a consequence, producing countries, now face multi-layered trade barriers before their products gain access to importing markets.